Short-term effects of X-ray on viscoelastic properties of epithelial cells. (May 2019) - Heydarian, Ashkan; Khorramymehr, Siamak; Vasaghi-Gharamaleki, Behnoosh
Examining the effects of ionizing radiation on the living cell is significant due to its usage in recent centuries. Investigations into the long- and short-term effects of ionizing radiation began simultaneously with its discovery. Previous studies were done on the effects of radiation on cell DNA or the biochemical cycle based on the electromagnetic radiation wavelength, intensity, and exposure time. Considering some dependent parameters like cell communication, the differentiation and the mechanical interactions of intercellular environment, and cell mechanical properties, the effects of ionizing radiation on the viscoelastic properties of cells seem to be important. The current research investigated the short-term biomechanical effects of ionizing radiation and examined the mechanical properties of cells using magnetic tweezer cytometry with nanomagnetic particles. To evaluate these effects, cells were incubated with nanomagnetic particles and then separated into controlled and irradiated groups. A 3 mGy cm 2 X-ray was radiated to the irradiated group for 0.02 s. The dishes of both groups were inserted into magnetic tweezer cytometry for applying a magnetic force pulse, and the cell membrane displacement was detected by an image processing system. The creep response of the membrane was determined for viscoelastic model curve fitting. The frequency responses of the model for both groups were calculated. The results showed that radiation could decrease cell extensibility from 0.084 ± 0.001 to 0.019 ± 0.001 µm and change the storage and loss modulus as the indicator of the viscoelastic property of the material. This research explains that radiation could affect cellular mechanical properties.